Analisis Pengaruh Kualitas Pelayanan Posyandu dan Pengetahuan Ibu Terhadap Sikap dan Implikasinya Terhadap Perilaku Ibu Datang ke Posyandu di Wilayah Kerja Puskesmas Sukaraja Kabupaten Sukabumi Dengan Metode SEM PLS - Nesda, Ajeng Setia; Yuliaty, Farida; Malik, Rahadian; Kosasih, Kosasih; Rahmiyati, Ayu Laili (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research aims to analyze the influence of the quality of Posyandu services and maternal knowledge on attitudes and their implications for maternal participation behavior in bringing toddlers to Posyandu in the working area of UPTD Puskesmas Sukaraja, Sukabumi Regency. This effort is crucial as part of a national program to reduce stunting rates by enhancing community participation in monitoring child growth and development. The study was conducted quantitatively using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with 97 respondents, utilizing SmartPLS 3.0 software. The results indicate that the quality of Posyandu services, maternal knowledge, attitudes, and maternal participation behavior are all categorized as good. Specifically, the quality of Posyandu services significantly affects maternal attitudes but does not have a significant impact on maternal participation behavior. Conversely, maternal knowledge positively influences both attitudes and participation behavior. Additionally, maternal attitudes have a direct relationship with participation behavior. Simultaneously, the quality of Posyandu services and maternal knowledge exert a moderate influence on attitudes and a strong influence on maternal participation behavior. In indirect analysis, it was found that the quality of Posyandu services does not affect participation behavior through maternal attitudes, while maternal knowledge has a significant impact through these attitudes. These findings underscore the importance of enhancing maternal knowledge as a primary strategy to encourage active participation in Posyandu. Furthermore, improvements in Posyandu service quality, particularly regarding physical and operational aspects, are necessary to maintain and enhance community trust. The recommendations from this study are expected to serve as a reference for policymakers in designing more effective interventions aimed at reducing stunting rates.